Fungsi Gereja Sebagai Entrepreneurship Sosial dalam Masyarakat Majemuk - Erman Sepniagus Saragih (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2019)
There is a tendency that the church has not been maximal in carrying out its social functions when viewed from the issue of a pluralistic community context. The church must actively transform the deacon, specifically alleviating the social problems surrounded. This study aimed to describe the model of transformation deaconal mission into the form of Christian entrepreneurs. By using literature review and descriptive methods, the conclusions obtained is: The church must be able to foster a sense of solidarity starting from inside the church to outside through the economic empowerment of her people.AbstrakAda kecenderungan bahwa gereja belum maksimal dalam menjalankan fungsi sosialnya ketika ditinjau dari persoalan konteks masyarakat majemuk. Gereja harus giat bertransformasi diakonia, secara khusus pengentasan masalah sosial yang berada disekitarnya. Kajian ini bertujuan untuk mendeskripsikan model transformasi misiologis diakonial dalam bentuk entrepreneur kristiani. Dengan menggunakan kajian literatur dan metode deskriptif, maka kesimpulan yang diperoleh adalah: Gereja harus dapat menumbuhkan rasa solidaritas dimulai dari jemaat hingga ke luar gereja melalui pemberdayaan ekonomi uma